Facile fabrication of TaON/Bi2MoO6 core–shell S-scheme heterojunction nanofibers for boosting visible-light catalytic levofloxacin degradation and Cr(VI) reduction - Li, Shijie; Wang, Chunchun; Cai, Mingjie; Yang, Fang; Liu, Yanping; Chen, Jialin; Zhang, Peng; Li, Xin; Chen, Xiaobo (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
[Display omitted] •TaON/Bi2MoO6 core–shell S-scheme heterojunction nanofibers were constructed.•TaON/Bi2MoO6 exhibited high catalytic activity for LEV and Cr(VI) removal.•The LEV degradation pathway and the detoxification performance were analyzed.•TaON/Bi2MoO6 boosts charge separation, redox capability and ROS production. Developing excellent photocatalysts for antibiotics degradation and Cr(VI) reduction is of vital significance but still a big challenge. Herein, novel S-scheme heterojunction of TaON/Bi2MoO6 with a core–shell structure is constructed via an electrospinning-calcination-nitridation approach, where 2D Bi2MoO6 nanosheets are uniformly and firmly anchored on the surface of 1D TaON nanofibers. The optimal TaON/Bi2MoO6 with the TaON/Bi2MoO6 molar ratio of 1:1 manifests the highest catalytic activity towards levofloxacin (LEV) antibiotic degradation and Cr(VI) reduction under visible light. The exceptional photocatalytic performance is probably due to the synergistic effect of the favorable core–shell fiber-shaped structure and S-scheme hetero-structure, which enables the strong interfacial interaction between the constituents for effectively improving the visible-light absorption, boosting the separation and utilization efficiency of electron-hole pairs, and retaining the charge carriers with stronger redox capabilities. Of note, TaON/Bi2MoO6 possesses excellent stability and reusability. Photo-generated h+, •OH, and •O2– are the main reactive species accounting for LEV degradation, the detailed LEV degradation pathways are elucidated by detecting the intermediates using HPLC–MS and the toxicity of the intermediates are assessed by quantitative structure–activity relationship (QSAR) method. In addition, •O2– and e– are primarily responsible for Cr(VI) reduction. Further, a possible photocatalytic reaction mechanism for removal of LEV and Cr(VI) is proposed. This study provides some insights in fabricating high-performance S-scheme heterojunction photocatalysts for the efficient water purification.